Private Governance of Biodiversity and Ecosystem Services: Findings From Nordic Forest Companies - D'Amato, Dalia; Matthies, Brent Davis; Hahn, Thomas; Toppinen, Anne (Frontiers in Sustainability, 2022)
This study examines the role of business organisations in co-governing biodiversity and ecosystem services (BES) using a phenomenon-based approach and bridging business management literature, ecosystem services literature and environmental governance literature. The empirical analysis includes twelve Nordic forest corporations considered market leaders in Finland, Sweden and Norway. Using content analysis of corporate sustainability reports and managerial interviews, we recorded 127 company-led measures addressing BES and we categorised them into seventeen types (e.g. land use planning and restoration, mobilization of financial resources for conservation, partner auditing, capacity building and consultation with stakeholders). For each BES measure, we also identified the BES issues being addressed (e.g. climate regulation, soil maintenance, cultural values); company motivation (i.e. compliance, strategic, profit-seeking); the stakeholders/beneficiaries involved (e.g. employees, forest owners, experts, local communities, public administration, NGOs); and the private governance instruments used for implementing the measure (i.e. regulatory, economic, information and rights-based instruments). The findings suggest that practices such as monetary valuation, biodiversity offsets and green bonds are emerging as profitable or strategically interesting options for Nordic forest companies. However, well-established practices, such as forest inventory, partner auditing and land sparing, continue to be the backbone of private BES governance among the leading companies examined. Although not directly motivated by compliance, private governance measures are largely nested in legislation. The contribution of this study includes reflections of relevance for both the scholarly and managerial realms. From a scholarly perspective, we further elaborate an understanding of BES management and governance from an organisational perspective. From a managerial perspective, we provide and discuss an overview of potential measures that forest companies can implement to address biodiversity and other socio-ecological issues at the land-use level.